Gibsonism: Ecologies of Architecture - Radman, Andrej 1968- (Delft Radman, 2012)
There is widespread commitment to indirect realism and reductionism among architects. As Robin Evans diagnosed, "we are landed not only with a picture theory of vision, but with a pervasive picture method of construction for manufactured objects as well." We see with our eyes, don't we? The answer is no. The founder of the ecological approach to perception insisted that we see with the eyes in the head on a mobile body supported by the ground, the brain being only the central organ of a complete visual system. The dissertation seeks to invigorate James Jerome Gibson's radical empiricism by exploring his unwitting affiliation with Gilles Deleuze's anti-representationalism
Keywords: Gibson, James J. -- 1904-1979; Architecture; Empiricism